Water flow simulation in a pelton turbine bucket with variable bucket dimensions using computational fluid dynamic - Muhammad Idris; Weriono Weriono; M Dalil; Indra Hermawan; Joko Joko; Achmad Jusuf Zulfikar; M.Y. Yuhazri (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
Today, especially among industrialized and developing nations, the usage of renewable energy sources is growing in popularity as a means of supplying energy needs. One of the renewable energy sources that is now being heavily exploited in Indonesia is the potential of water that may be used as a source of electrical energy by establishing a hydroelectric power plant (PLTA). One of the turbines that is frequently used in hydropower plants as a part that may transform water's kinetic energy into mechanical energy is the Pelton turbine. There is not a lot of literature on the design of Pelton turbine buckets. In order to determine the most ideal bucket dimensions that can be used with Pelton turbines, this study presents the conceptual and experimental components of the design and analysis of Pelton turbines based on bucket variations. AutoCAD was used to model the bucket and Pelton turbine, and ANSYS Fluent was used to perform the simulation so that results could be analyzed later. By comparing the simulated data of the blade variants 1 and 2, the ideal blade dimension variation is identified by the blade simulation of variant 1. The blade variation 2 with average torque of 5.859 Nm, average angular velocity of 40.822 rad/s, and average power of 242,970 watts is the most ideal blade. With an average torque of 4,735 Nm, an average corner speed of 40,404 rad/s, and an average power of 196,794 W, the blade 3 model has lower values